2015
DOI: 10.1515/multi-2014-0066
|View full text |Cite
|
Sign up to set email alerts
|

Translation meets cognitive science: The imprint of translation on cognitive processing

Abstract: Translation has long played a role in linguistic and literary studies research. More recently, the theoretical and methodological concerns of process research have given translation an additional role in cognitive science. The interest in the cognitive aspects of translation has led scholars to turn to disciplines such as cognitive linguistics, psycholinguistics or even neurology in search of innovative approaches and research methods. This paper reviews current issues in translation studies, and a variety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…They have come to recognize that translation is also a highly complex cognitive task. As such, cognitive factors have helped us understand the study of translation in the form of problem solving and puzzle solving activities, as well as fine sensory-motor abilities ( Rojo et al, 2014 ; Rojo, 2015 ). The various cognitive elements involved therefore make these processes exceptionally difficult to master and thus remain mostly unexplained.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…They have come to recognize that translation is also a highly complex cognitive task. As such, cognitive factors have helped us understand the study of translation in the form of problem solving and puzzle solving activities, as well as fine sensory-motor abilities ( Rojo et al, 2014 ; Rojo, 2015 ). The various cognitive elements involved therefore make these processes exceptionally difficult to master and thus remain mostly unexplained.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the area of technological innovation, their work is the subject of scholarly debate, as there is no single computer program that can create a highly accurate translation. Although such technology has been highly useful in areas such as STEM sciences, no technological innovation thus far has managed to create a faultless translation output, making this line of research even more challenging ( Rojo, 2015 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The psycholinguistics of translation has strongly appealed to translation researchers in recent years, with some scholars beginning to realize that psychological mechanisms and characteristics may have influential effects on different translation processes (Rojo, 2015;Rojo & Caro, 2018). These researchers have come to the realization that the translation processes and their final product (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Related to conceptual knowledge and its organization in the brain, the second commonly studied area of interpretation is cognitive. Several studies have found that conceptual knowledge is organized as a network of mutually interconnected nodes, the activation of which represents the retrieval of information (Gillies, 2019;Guo, 2016;Ning et al, 2020;Rojo Lopez, 2015). Language is a key element in transferring information, a specific mental entity that is prone to constant development.…”
Section: Introductionmentioning
confidence: 99%